DISTANT VIKINGS: A MANIFESTO. Issue 1 (15th January 2019) - Price, Neil
ABSTRACT: This paper addresses some contemporary challenges in approaching the Viking Age, specifically the need for new interpretive models that we can bring to bear on its material culture, ideally drawn from cross‐cultural, comparative analyses across time and place. A range of potential case studies is presented here from the island states of Oceania, across the broad socio‐cultural networks of the Pacific. By looking at familiar Scandinavian sites and finds through a different lens, we can view them afresh and arrive at new understandings of this critical period of Northern history by comparison with these 'distant Vikings'.